Importance of body expression in the cognitive development of early childhood education students: A systematic review - Cetre Vásquez , Roxana Paola; Macías Alvarado, Jessica Mariuxi; Jessica Marlene, Ramos Anchundia; Cetre Vásquez , Ángela Andrea (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The aim of this study was to determine the importance of body language in the cognitive development of early childhood education students. The methodology consisted of a systematic review, in which a bibliographic search of scientific articles was carried out in databases such as: SCOPUS, PROQUEST, SPRINGER, TAYLOR & FRANCIS and SCIELLO. As a search strategy, the Boolean operators “AND” and “OR” were used, in order to obtain the greatest possible number of relevant articles before their exclusion. The analysis of the reviewed studies highlighted that bodily expression, through activities such as play, dance and physical movement, has a positive and significant impact on the cognitive development of children in early education. These activities not only improve motor development but also promote key skills such as memory, attention, perception and concentration, essential for early learning. It is concluded that body expression must be systematically integrated into the educational curriculum to promote comprehensive development in early childhood education. Ultimately, body language plays a crucial role in children's cognitive development, integrating physical and mental skills that are essential for their early learning.